Kinematic Gait Analysis of the Trot in Healthy Mixed Breed Dogs - Allen, K.; DeCamp, C. E.; Braden, T. D.; Balms, Michelle (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Computer aided kinematic and synchronized force plate gait analysis were used to characterize joint movement in 14 large mixed breed dogs at a trot. A curvilinear relationship of joint angle to time was described, for three forelimb and three hindlimb joints. Two peaks of maximum extension, one preceding the onset and at the end of stance phase were observed for the femorotibial, tarsus and cubital joints. The carpus, scapulohumeral and coxofemoral joint exhibited one peak of maximum extension. The variance in joint angle measurement was calculated for repeated trials for a given dog and for differences between dogs using a 2-factor repeated measures ANOVA. The mean variance for all joints except the carpal joint for trial repetition was 12.6 (degrees)2 (range, 2.6-23.9) and for differences between dogs 6.2 (degrees)2 (range, 1.0-11.3). The carpal joint exhibited greater variation with a mean variance, attributable to trial repetition, of 42.5 (degrees)2 (range, 39.4-44.3) and a variance between dogs of 52.4 (degrees)2 (range, 18.5-89.4).The results obtained would suggest that computer assisted kinematics is an accurate means of assessing joint angle movement in large mixed breed dogs with a low level of variance attributable to trial repetition and to differences between dogs, with the exception of the carpal joint. The sample of mixed breed dogs in this study is similar to dogs that would be seen in a clinical sample population. Our results suggest that computer assisted kinematics could be an important tool in providing objective information on gait, in clinical and research studies, using mixed breed dogs.This study describes the trot in 14 large mixed breed dogs using computer aided kinematic and force plate gait analysis techniques. Variances in fore and hindlimb joint angle measurements were deter-mined, for a given dog, by repeated trials and for differences between dogs. The measured variances were low in all joints except the corpus, despite diverse dog conformation in the study.
Keywords: Mixed breed; trot; kinematic gait analysis; variance; dynamic joint angles